Language strategies to develop english listening skill in the students of 7mo año de educacion básica, unidad educativa Doctor Emilio Uzcátegui, at Cebadas, Guamote canton, Chimborazo province, in the academic year 2014-2015 - Illicachi Rojas, Gabriela Katherin (2016)
The topic of this research is “Language Strategies to develop the English listening skill in the students of 7mo Año de Educación Básica”. The purpose of this work is to explore strategies in order to create suitable activities to help the students develop their listening skill inside and outside the EFL (English as a foreign language) classroom. Richards states “listeners can be taught effective ways of approaching and managing their listening” for this reason, it is very important to apply the most useful strategies to help students develop this skill. Since, the listening skill is considered the most important one, it is essential for kids to develop it, so they become good listeners. Thus, the acquisition of the new language will be more productive